A method for determining transverse permeability of tight reservoir cores by radial pressure pulse decay measurement. Issue 10 (9th October 2016) - Yang, Zehao; Dong, Mingzhe; Zhang, Shaojie; Gong, Houjian; Li, Yajun; Long, Feifei
Abstract: A transverse pressure pulse decay (TPPD) method is presented to measure transverse permeability of tight reservoir cores in a cell with finite volume. Given appropriate assumptions, a mathematical model based on the specially designed experiment is formulated, and its general solution is proposed. Early‐time and late‐time techniques are further presented for convenient postprocessing applications of experimental data. Meanwhile, sensitivity analysis of TPPD method is given. It is found that a good TPPD experimental principle can be obtained by adjusting test gas, experimental pressure, dimension of core sample, and volume ratio ( λ ). The volume ratio error ( λ error ) analysis reveals the following: (1) a larger λ error results in increased transverse permeability error ( k error ); (2) the volume ratio ( λ ) is better not very close to 0.754; (3) when λ is equal to or greater than 1, the k error resulting from λ error is monotonic decreasing as the volume ratio increases. In practice, λ is usually equal to or greater than 1 due to the very small pore volume of a tight core. But this does not mean that the volume ratio should be as large as possible. The reason for this is that a pressure transducer with higher resolution is needed to record pressure change. That means experimental apparatus is much more costly. And such a TPPD experiment requires a much longer time to attain the late‐time straight line behavior. The best choice is to find an optimal balance point among experimental cost, time, and accuracy. Key Points: Transverse pressure pulse decay (TPPD) method is proposed to measure transverse permeability of tight cores in a cell with finite volume The general solution for the method has been obtained. Early‐time and late‐time techniques are presented The optimal principle of TPPD experiment is discussed in detail